Microbial life-history strategies and genomic traits between pristine and cropland soils - Dan He; Zhongmin Dai; Shuxun Cheng; Haojie Shen; Jiahui Lin; Kankan Zhao; Jorge L. Mazza Rodrigues; Yakov Kuzyakov; Jianming Xu (mSystems)
ABSTRACT Microbial life-history strategies [inferred from ribosomal RNA operon (rrn) gene copy numbers] and associated genomic traits and metabolism potentials in soil significantly influence ecosystem properties and functions globally. Yet, the differences in microbial strategies and traits between disturbed (cropland) and pristine soils, along with their dominant driving factors, remain underexplored. Our large-scale survey of 153 sites, including 84 croplands and 69 pristine soils, combined with long-term field experiments demonstrates that cropland soils support microbial communities with more candidate r-strategies characterized by higher rrn copy numbers and genomic traits conducive to rapid resource utilization. Conversely, pristine soils tend to host communities aligned with more candidate K-strategies marked by high resource use potentials. Elevated nitrogen (N) and phosphorus (P) levels in cropland soils emerge as key factors promoting these candidate r-strategies, overshadowing the influence of organic carbon content, soil structure, or climatic conditions. Results from four long-term field experiments also corroborate that sustained N and P inputs significantly elevate rrn copy numbers, favoring these candidate r-strategists. Our findings highlight that land use and fertilization practices critically shape microbial life-history strategies, with nutrient availability being a decisive factor in increasing the r-strategists in cropland soils.IMPORTANCEMicrobial life-history strategies and genomic traits are key determinants shaping the response of populations to environmental impacts. In this paper, 84 cropland and 69 pristine soil samples were studied, and microorganisms in two ecosystems were categorized into two types of ecological groups using the classical copiotroph–oligotroph dichotomy, promoting a general understanding of the ecological roles of microorganisms. This study is the first to investigate the microbial life-history strategies under different land uses across five climatic zones in China. The results showed that the microbes in cropland soils are more copiotrophic than pristine soils. It also demonstrates that elevated levels of nitrogen and phosphorus in cropland soils are the key factors promoting these r-strategies. This observation emphasizes the critical role of nutrient management in shaping microbial community dynamics and ecosystem functioning and lays the foundation for predicting the response of microbial community composition under resource perturbation.